Case report: Posterior reversible encephalopathy syndrome, an adverse effect of lenvatinib and pembrolizumab combination therapy, in a patient with advanced endometrial cancer - Matsuura, Yuki; Nishida, Haruka; Kosaka, Takashi; Shigekawa, Kazuyuki; Takasaki, Kazuki; Ichinose, Takayuki; Hirano, Mana; Hiraike, Haruko; Nagasaka, Kazunori (Frontiers in Oncology, 2023)
Background: Lenvatinib-pembrolizumab combination (LEAP) is an approved therapy in Japan for advanced endometrial cancer, based on the data from the KEYNOTE-775 clinical trial. We report a case of posterior reversible encephalopathy syndrome (PRES) in a patient who received LEAP therapy for advanced endometrial cancer. Case presentation: A 53-year-old patient with stage IVB endometrial cancer having rectal metastases, after four cycles of paclitaxel-carboplatin therapy, was found to have increased rectal invasion, peritoneal dissemination, and multiple paraaortic lymph node metastases. She was treated with LEAP therapy and discharged on day 12 without adverse events, except for mild anemia on day 11 of treatment. She was carefully managed in the outpatient department, but on day 18, she was admitted to the emergency department with severely impaired consciousness and generalized seizures. Computed tomography of the head and lumbar tap showed no abnormal findings, and the seizures resolved with anticonvulsant medication alone. Based on a thorough physical examination and findings on magnetic resonance imaging (MRI), which showed high signal intensity in the left occipital lobe, encephalopathy, rather than encephalitis, was the likely diagnosis. Symptomatic improvement was observed, and pembrolizumab monotherapy was resumed. Conclusions: If consciousness is impaired during LEAP treatment, it is necessary to differentiate between immunogenic encephalitis caused by pembrolizumab or encephalopathy caused by lenvatinib. MRI and lumbar tap can help in distinguishing between the two and diagnosing the responsible drug.